2002
DOI: 10.2165/00003495-200262030-00006
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Valerate/Dienogest

Abstract: Estradiol valerate 2mg/dienogest 2mg is an oral estrogen/ progestogen formulation that has been approved throughout the European Union for the treatment of climacteric symptoms in postmenopausal women. Dienogest is a progestogen that combines the properties of both progesterone and 19-nortestosterone derivatives. It has moderate affinity for the progesterone receptor, significant antiproliferative and antiandrogenic activity, and produces secretory transformation of the endometrium. Estradiol valerate is an es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Fourth, it was impossible in this explorative preliminary study to evaluate maternal serum concentrations of other biological forms of estrogen and progestogen. The choice to analyze 17β-estradiol in OD was based on the pharmacokinetic and pharmacodynamics profile of estradiol valerate [25,26]. This study has several strengths.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, it was impossible in this explorative preliminary study to evaluate maternal serum concentrations of other biological forms of estrogen and progestogen. The choice to analyze 17β-estradiol in OD was based on the pharmacokinetic and pharmacodynamics profile of estradiol valerate [25,26]. This study has several strengths.…”
Section: Discussionmentioning
confidence: 99%
“…Their climacteric symptoms had been evaluated and Kupperman index scores were found to be 78.5%, 74.5% and 75% respectively [14][15][16]. Although a number of studies have reported physical side effects (constipation, bloating and breast pain) and psychological side effects (depression, fatigue, irritability) resulting from medroxyprogesterone acetate use, these were not observed in prospective randomized studies [17].…”
Section: Discussionmentioning
confidence: 99%
“…Commercialisé en France par les laboratoires Schering AG à la dose de 2 mg/jour en association au valé-rate d'estradiol depuis 2003, il s'administre à la dose d'un comprimé par jour en continu dans l'indication « traitement hormonal substitutif (THS) des symptômes de déficit en estrogènes chez les femmes ménopausées depuis au moins un an, et non hystérectomisées ». La tolérance de Climodiène ® sur le plan des saignements s'est avérée bonne [12], avec 67 et 85 % d'aménorrhées respectivement à trois et 12 mois de traitement. Climodiène ® s'est révélé efficace sur les plaintes climatériques et bien toléré dans une étude de phase III [13] sur 1501 femmes traitées pendant un an.…”
Section: Discussionunclassified